# prove alpha and beta equations are equivalent

Discussion in 'Homework Help' started by Spartan, Oct 13, 2007.

1. ### Spartan Thread Starter New Member

Oct 13, 2007
2
0
How do I go about varifing that:

alpha = Ic/Ie and alpha = beta/beta +1

see attachment for what I have done so far.

Thank you,

File size:
19 KB
Views:
133
2. ### hgmjr Moderator

Jan 28, 2005
9,030
214
Your two base assumptions are incorrect.

Beta = Ic/Ib and Ie = Ic + Ib

hgmjr

Istiaque Ahmed likes this.
3. ### Spartan Thread Starter New Member

Oct 13, 2007
2
0
o.k., your right Beta = Ic/Ib . I screwded that up. Thank you, but to prove that
the two alpha equations are equivalent, we will need to take the alpha = beta/beta+1 and put it in common terms. alpha = Ic/Ie. So, to get rid of the betas, beta = Ic/Ib, Ie=Ic + Ib, so if I wanted to get Ib alone, I could go Ib = Ie-Ic. so I can replace Beta with that equation. However, I need to get rid of the Ib component. Am I going about this the right way or is there an easier way? I need to factor this all right, correct?

4. ### hgmjr Moderator

Jan 28, 2005
9,030
214
You should be able to find in your textbook the expression that equates Ic to Ib. You should also be able to find in your textbook the expression that equates Ie to Ib.

You can then substitute into the expression alpha = Ic/Ie, Ic as a function of Ib and Ie as a function of Ib. If you do it correctly, Ib will cancel out and leave you with the expression for alpha in terms of beta only.

hgmjr